1999
DOI: 10.1046/j.1365-2362.1999.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

The growth and the control of human immunodeficiency virus in the lung: implications for highly active antiretroviral therapy

Abstract: In recent years, it has become apparent that the lung is an important niche for the proliferation of human immunodeficiency virus (HIV), which may have implications for highly active antiretroviral therapy (HAART). The lung itself is a major site for the opportunistic infections associated with the progression to acquired immune deficiency syndrome (AIDS), specifically Pneumocystis carinii, Myobacterium tuberculosis and pyogenic bacteria. These cases of active pulmonary complications are direct indicators of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 63 publications
1
24
0
2
Order By: Relevance
“…Activated MMPs also exert significant control over inflammation, modulating the recruitment of leukocytes into the lung [7,12]. Since HIV1 ؉ smokers have a higher incidence of emphysema than HIV1 Ϫ smokers and since alveolar macrophages are known to be activated in HIV1 ϩ individuals [13][14][15][16][17][18][19][20] and in HIV1 Ϫ smokers [8], we hypothesized that AM of HIV1 ϩ smokers may up-regulate the expression of MMPs to a higher extent than HIV1 -smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Activated MMPs also exert significant control over inflammation, modulating the recruitment of leukocytes into the lung [7,12]. Since HIV1 ؉ smokers have a higher incidence of emphysema than HIV1 Ϫ smokers and since alveolar macrophages are known to be activated in HIV1 ϩ individuals [13][14][15][16][17][18][19][20] and in HIV1 Ϫ smokers [8], we hypothesized that AM of HIV1 ϩ smokers may up-regulate the expression of MMPs to a higher extent than HIV1 -smokers.…”
Section: Introductionmentioning
confidence: 99%
“…THE LUNG IS AN IMPORTANT RESERVOIR of HIV and a site for HIV replication (44). HIV is uniformly detected in alveolar macrophages of infected pediatric patients and in the majority of adult patients (30).…”
mentioning
confidence: 99%
“…In spite of highly active antiretroviral therapy (HAART) suppression of HIV-1 replication in T cells, various reservoirs, including AMs, dendritic cells, and other monocyte-derived tissue macrophages continue to harbor the virus (3,4). We have previously shown that if AMs are infected with an E1 2 E3 2 adenovirus (Ad) gene transfer vector before in vitro HIV-1 infection, subsequent replication of HIV-1 by the AM is markedly suppressed independently of the transgene in the Ad vector (5).…”
mentioning
confidence: 99%